Multiple Intelligences-Based Learning Strategies for Islamic Religious Education in Private Elementary Schools - Lubis, Hernawan Syahputra; Lubis, Saiful Akhyar; Daulay, Nurussakinah (Al-Hayat: Journal of Islamic Education, 2024)
This research examines the application of multiple intelligences-based learning strategies in Islamic religious education learning in several elementary schools in Medan, including planning, implementation, and evaluation, as well as supporting and inhibiting factors, to assess the effectiveness and challenges in supporting diverse learning. This research uses qualitative methods with a phenomenological approach to examine multiple intelligences-based learning strategies in Islamic religious education in four Elementary Schools (SD) in Medan, namely Panca Budi Private Elementary School, Anbata Plus Elementary School, Shafiyyatul Amaliyah Elementary School, and Brigjend Katamso Private Elementary School, through observation, interviews and documentation, with data analysis using the Miles and Huberman model and testing the validity of the data through triangulation. The research results show that teachers plan to prepare syllabi, lesson plans, and assessments based on multiple intelligence strategies. A multiple intelligences approach to religious learning recognizes each student's unique intelligence, increases their engagement, and expands the development of numerous relevant aspects of intelligence. This strategy encourages students' learning motivation and creates an inclusive environment while teachers adapt the centre's syllabus and use multiple learning methods. Evaluation is based on the student's learning process and intelligence, with the school and parents actively supporting this process. Although supporting factors include teachers' mastery of the material and student's interest in learning, some obstacles include limited perceptions about Islamic religious education, a limited evaluation system, and a lack of supervision of teaching by school principals and school supervisors. The implications of this research contribute to educational literature on integrating multiple intelligence strategies in religious learning, which opens up space for further research development.